Operation and energy management of hybrid AC/DC building microgrid - Guan, Shaokang (Nanyang Technological University, 2022)
Microgrid has become a more attractive option in modern power system due to its advantages such as greater stability, lower energy losses and less pollution to the environment. A microgrid is a localized group of distributed generators including renewable energy sources (RESs), energy storage systems (ESSs) and AC/DC loads which are integrated together by either an AC network, DC network or hybrid AC/DC network. However, the intermittency of RES and the high cost of ESS should be carefully considered in the planning and operation stage. A microgrid can operate in a stand-alone or grid tied mode which depends on loads and available power generation from distributed renewable sources and power from bulk power system. Therefore, an optimal energy management system (EMS) for control and operation is very important for future building microgrids. Energy management is the process of tracking and optimizing energy consumption to conserve usage in a building. An energy management can also make sure that the power supply is equal to load demand. There are two main factors which have a great impact on energy management system. One is dynamic pricing of electricity market. Different prices will directly influence the energy management decisions of microgrids. Another is capacity and cost of energy storage system. In this dissertation, based on a typical architecture of hybrid AC/DC microgrids, an energy management system is presented for microgrids. Each part of microgrid is modelled according to its respective output characteristics. In addition to the basic conditions and factors, such as the power flow constraints, the intermittency of renewable energy source and healthy constraints of ESS are also considered in the modelling process. Without loss of generality, some real dataset and reliable and mature model structures are applied. Finally, by applying IPOPT solver in Python, the feasibility of this energy management system is verified. By using this energy management system, the comprehensive operation cost of microgrid has also been reduced to a great extent, which has certain theoretical guiding significance and practical engineering value for the overall economic operation of a microgrid.